KOMPARASI PENDAPATAN USAHATANI PADA BEBERAPA KOMBINASI SISTEM OLAH TANAH DAN PERTANAMAN - Yuliarti, Ellys (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
This research was conducted in research station at Bogor Agricultural University from october 1992 to July 1993. It was aimed to compare income of farming system under various of land tillage and plant. Analysis of varian was applied to examine the influence of various tillage system the results showed that minimum tillage and conventional could decreser farmers income through in the second season monoculture and multicropping systems.